2008
DOI: 10.1088/1748-6041/4/1/015007
|View full text |Cite
|
Sign up to set email alerts
|

In vitroinvestigations of bone remodeling on a transparent hydroxyapatite ceramic

Abstract: The light microscopic examination of cells directly on bioceramic materials in the transmission mode is impossible because many of these materials are opaque. In order to enable direct viewing of living cells and to perform time-lapse studies, nearly transparent bioceramic materials were developed. A dense and fine-grained transparent hydroxyapatite (tHA) was processed by a gel-casting route followed by low-temperature sintering (1000 degrees C). By virtue of its transparency, direct visualization of cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…in this study, we used hydroxyapatite (hA) as bone graft substitute because in vitro/vivo studies have reported favorable clinical results following surgical treatment of intrabony defects with hydroxyapatite graft materials (14,18,23,38). our results showed that the use of hA granules did not cause any undesirable reaction.…”
Section: Resultsmentioning
confidence: 99%
“…in this study, we used hydroxyapatite (hA) as bone graft substitute because in vitro/vivo studies have reported favorable clinical results following surgical treatment of intrabony defects with hydroxyapatite graft materials (14,18,23,38). our results showed that the use of hA granules did not cause any undesirable reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a release of factors by endothelial and osteoblast cells in co-culture supported proliferation and differentiation was suggested to ultimately result in microcapillary-like vessel formation and supported a neo-tissue growth within the scaffold [408]. More to the point, investigation of rat calvaria osteoblasts cultured on transparent HA bioceramics, as well as the analysis of osteogenic-induced human bone marrow stromal cells at different time points of culturing indicated to a good http://ccaasmag.org/BIO cytocompatibility of HA bioceramics and revealed favorable cell proliferation [368]. Positive results for other types of cells have been obtained in other studies [206,363,364,367].…”
Section: Bioactivitymentioning
confidence: 98%
“…Thus, transparent calcium orthophosphate bioceramics (Fig. 5) [361] have been prepared and investigated [204,206,289,292,[361][362][363][364][365][366][367][368][369][370]. They can exhibit an optical transmittance of ~ 66 % at a wavelength of 645 nm [370].…”
Section: Possible Transparencymentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxyapatite is a ubiquitous part of the vertebrate bone. Hydroxyapatite ceramics become easily integrated and also prove enough primary stability (John, Varma et al 2009;Nair, Bernhardt et al 2009;Nair, Varma et al 2009). Beta-tricalciumposphate is a completely resorbable scaffold with high purity.…”
Section: In Vitro 3d Culture Choice Of Scaffoldmentioning
confidence: 99%